Business Innovation for Micro, Small and Medium Enterprises in Jember - Kantun, Sri; Sedyati, Retna Ngesti Sedyati; Tiara, Tiara; Mujib, Muhammad Asyroful; Triyanto, Jefri Rieski; Sukidin, Sukidin; Widayani, Anna (BRILIANT: Jurnal Riset dan Konseptual, 2022)
Along with the rapid development of MSMEs, it requires business actors to innovate. Innovating is carried out according to the needs and tastes of today's consumers. Hundreds of MSMEs in Jember can still survive running their businesses during the Covid-19 pandemic, so they should be used as examples of best practices for other MSMEs in Indonesia. One of the products that are currently superior is souvenirs from Jember Regency. This study aims to identify and examine business innovations carried out by the souvenir center of Jember Regency.